TAHLÎL AL KITÂB AL MADRASY LI AL LUGHAH AL ‘ARBÎYAH LI AL SHAFFI AL SÂB’I LI WAZÂRAH AL SYÛN AL DÎNÎYAH ‘ÂM 2020 ‘ALA NAZRÎYAH I’IDÂD AL MAWÂD AL T’ALÎMÎYAH LI RUSYDI AHMAD TU’AIMAH - Khair, Miftahul; Firmansyah, Muh. Guntur; Rosyidi, Abdul Wahab; Muhaiban, Muhaiban (STIQ Amuntai, 2023)
In this study, we discussed the results of the analysis of the Arabic language textbook for the Ministry of Religious Affairs seventh grade in 2020 according to the theory of preparing educational materials for Rushdi Ahmed Tuaima—the basic. The researcher used analytical research, a qualitative approach, type of document or textual study (document study). They examined the results of this analysis that the number of its pages is 144 pages on average, each lesson contains 22 pages, this book has six errors in the formation of letters and the typographical errors in this book are two, and the number of lessons in the book for teaching the Arabic language for the seventh grade is less than The number of classes expected to be taught. The language level in this textbook is the beginner level, and the proposed duration of the book is sufficient to teach the book in one year. We found that the teacher in some language skills still plays a decisive role in the learning process, so communication channels must be diversified to enhance the learning and teaching experience. This textbook included various linguistic situations from vocabulary, texts, dialogue, composition, and listening. Also, various activities can help students improve their language skills and prepare them to deal effectively with Arabic in daily life.